2003
DOI: 10.1016/s0378-1097(03)00781-x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of an aldehyde oxidase fromPseudomonassp. KY 4690

Abstract: An aldehyde oxidase, which oxidizes various aliphatic and aromatic aldehydes using O 2 as an electron acceptor, was purified from the cell-free extracts of Pseudomonas sp. KY 4690, a soil isolate, to an electrophoretically homogeneous state. The purified enzyme had a molecular mass of 132 kDa and consisted of three non-identical subunits with molecular masses of 88, 39, and 18 kDa. The absorption spectrum of the purified enzyme showed characteristics of an enzyme belonging to the xanthine oxidase family. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…These results suggested that the enzyme consisted of three non-identical subunits, as do ALODs from Pseudomonas sp. KY4690 and P. stutzeri IFO12695 (Uchida et al 2003(Uchida et al , 2005. Although the MM of the medium subunit of S. rimosus ATCC10970 ALOD was similar to those of the Pseudomonas ALODs, the MMs of the other subunits of the former ALOD were different from those of the Pseudomonas ALODs.…”
Section: Subunit Structurementioning
confidence: 93%
See 4 more Smart Citations
“…These results suggested that the enzyme consisted of three non-identical subunits, as do ALODs from Pseudomonas sp. KY4690 and P. stutzeri IFO12695 (Uchida et al 2003(Uchida et al , 2005. Although the MM of the medium subunit of S. rimosus ATCC10970 ALOD was similar to those of the Pseudomonas ALODs, the MMs of the other subunits of the former ALOD were different from those of the Pseudomonas ALODs.…”
Section: Subunit Structurementioning
confidence: 93%
“…After both electrophoreses, the sample was stained for protein with 0.25% Coomassie brilliant blue R-250. After native-PAGE, stain for enzyme activity was also done, as described previously (Uchida et al 2003). Standard proteins for SDS-PAGE used were rabbit muscle phosphorylase (MM, 97.4 kDa), bovine serum albumin (MM, 66.2 kDa), chicken egg albumin (MW, 45.0 kDa), bovine carbonic anhydrase (MW, 31.0 kDa), soybean trypsin inhibitor (MW, 21.5 kDa), and lysozyme (MW, 14.4 kDa) (BioRad Laboratories).…”
Section: Electrophoresismentioning
confidence: 99%
See 3 more Smart Citations